Office Reboot. - DE MONCHAUX, THOMAS (Architectural Record, 2023)
PROJECTS META FARLEY | NEW YORK | KOHN PEDERSEN FOX PHOTOGRAPHY BY CONNIE ZHAO "HACKING FARLEY." Other ready-made elements, described by Kassem as having a "garage aesthetic", include a ferroconcrete structural frame around the lobby and atrium that were left as KPF found them. This was the in-house name that Kohn Pedersen Fox (KPF) principal Hana Kassem and her team gave their task, undertaken between 2019 and 2023, of transforming some 700,000 square feet, across five stories, of midtown Manhattan's landmark Farley Post Office Building into office space for Meta, the parent company of Facebook.